2021
DOI: 10.1055/a-1388-5415
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone with Metformin Decreases Fasting, Post Prandial Glucose, and HbA1c in Type 2 Diabetic Patients

Abstract: Objective Antihyperglycemic activity of Thymoquinone (TQ) was evaluated in diabetic mouse model and patients. Methods TQ (50 mg/kg) was orally administered daily for 21 days in combination with metformin in diabetic mice and a reduction on blood glucose level was monitored. In human, a 90-day randomized study was carried out in 60 Type 2 Diabetes mellitus patients to evaluate safety and efficacy of TQ administration with metformin in a 3-arm study. Patients in arm 1 (T1) received 1 tablet of metformin SR 1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Synergistic antidiabetic activity of metformin (1000 mg /day) was observed by the addition of 1 or 2 tablets of Thymoquinone 50 mg daily for 90 days in 60 patients with type 2 diabetes mellitus, through further reduction in the levels of HbA1c and blood glucose. 56 Moreover, an experimental animal study using streptozotocin-induced diabetic rats determined that thymoquinone improves the antidiabetic activity of metformin synergistically through its antioxidant properties (decreased malondialdehyde [MDA] and augmented total antioxidant capacity [TAC]). 57 Hence, the patients taking this combination should be monitored for the signs and symptoms of hypoglycemia.…”
Section: Drug Interactions Possibility Of N Sativa With Modern Antidiabeticsmentioning
confidence: 99%
“…Synergistic antidiabetic activity of metformin (1000 mg /day) was observed by the addition of 1 or 2 tablets of Thymoquinone 50 mg daily for 90 days in 60 patients with type 2 diabetes mellitus, through further reduction in the levels of HbA1c and blood glucose. 56 Moreover, an experimental animal study using streptozotocin-induced diabetic rats determined that thymoquinone improves the antidiabetic activity of metformin synergistically through its antioxidant properties (decreased malondialdehyde [MDA] and augmented total antioxidant capacity [TAC]). 57 Hence, the patients taking this combination should be monitored for the signs and symptoms of hypoglycemia.…”
Section: Drug Interactions Possibility Of N Sativa With Modern Antidiabeticsmentioning
confidence: 99%
“…Eight studies were double-blinded and two studies [ 30 , 31 ] were single-blinded. Eleven studies were placebo-controlled, 4 studies used active control: metformin [ 32 , 33 ], received conservative management for diabetic nephropathy [ 34 ], atorvastatin + metformin [ 29 ], while 2 studies were non-controlled [ 28 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies were carried out in Iran ( n = 7), Egypt ( n = 2), Saudi Arabia ( n = 2), Pakistan ( n = 2), India ( n = 2), and Indonesia ( n = 1). All studies were done on adults ≥18 years with the majority up to 60 years with the exception of three studies up to 63 years [ 36 ] and 64 years [ 32 , 37 ]. The number of participants analysed ranged from 40 [ 38 ] to 99 [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For those who completed the study a decrease in glycated hemoglobin was observed after three months. A greater reduction in fasting blood glucose and postprandial blood glucose was also observed in both groups compared with the control group [ 100 ]. The study of the inhibitory activity of a hydroalcoholic combination (70%) of Morinda citrifolia , Trigonella foenum-graecum , and NS on pancreatic α-amylase showed that this combination at different doses was able to inhibit the activity of the enzyme.…”
Section: Pharmacological Properties Of Nigella Sativamentioning
confidence: 99%